Cinema reporter and the reconfiguration of Cartagena de Indias popular culture 1936-1957 (2011)
This article presents a discussion about the place that popular classes took in the construction of a Colombian cultural image, due to the fact that the upper classes wanted to promote a modernization of the country copying some of the Northern countries models. In Cartagena, the media, especially, the Mexican cinema in its golden age were signiicant for setting up some cultural meanings in the popular classes because they were growing little by little and were gaining space in a social model that expended a place in its origin. The social meanings were constructed by means of the melodrama, its features and its actions, which were molded in the collective conscience and were practiced in new feelings and styles in the daily life. The news reports in the Mexican magazine Cinema Reporter (1932 - 1958) and the cinema board seen in Cartagena at that time prove that fact.